Consumer Protection as a Factor of Destination Competitiveness in the European Union - Jelena Petrovic; Snežana Milicevic (Amfiteatru Economic Journal, 2017)
Many tourism destinations have enacted and implemented laws to protect residents as consumers that are relevance to tourists as consumers. In literature, consumer protection is not explicitly considered and analyzed in the area of destination competitiveness by research ers. This research article investigates the impact of cons umer protection on destination competitiveness in the European Union. Research results have pointed out that consumer protection represents a factor of destination competition because illicit commercial practices and consumer trust consumers as consumer indicators affect the value of the Enabling Environment subindex, while illicit commercial practices affect the value of Infrastructure subindex, and the consumer indicators mentioned in this way affect the destination competitiveness . At the same time, the results of the analysis indicate that the European Union member states that record the highest consumer confidence and the lowest level of illicit commercial practices also record the highest competitiveness as a tourism destination.
Keywords: F12; L83; D12; 330; destination competitiveness; consumer protection; tourists; European Union